Improving the permeance of hybrid polymer/metal–organic framework (MOF) membranes for organic solvent nanofiltration (OSN) – development of MOF thin films via interfacial synthesis. Issue 18 (14th May 2015) - Campbell, James; Davies, R. P.; Braddock, D. Christopher; Livingston, A. G.
<x xml:space="preserve">Abstract</x> Films of HKUST-1 were fabricated, via interfacial synthesis, on polymer supports. MOF thin film composite membranes (MOF-TFCs) have similar solute retentions as in situ growth (ISG) membranes; but permeances are over 3 times higher.